Stage-Dependent Impact of RIPK1 Inhibition on Atherogenesis: Dual Effects on Inflammation and Foam Cell Dynamics - Zhang, Yuze; Li, Huihui; Huang, Yonghu; Chen, Hong; Rao, Haojie; Yang, Guoli; Wan, Qing; Peng, Zekun; Bertin, John; Geddes, Brad; Reilly, Michael; Tran, Jean-Luc; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Atherosclerosis is an arterial occlusive disease with hypercholesterolemia and hypertension as common risk factors. Advanced-stage stenotic plaque, which features inflammation and necrotic core formation, is the major reason for clinical intervention. Receptor interacting serine/threonine-protein kinase 1 (RIPK1) mediates inflammation and cell death and is expressed in atherosclerotic lesions. The role of RIPK1 in advanced-stage atherosclerosis is unknown. Approach and Results: To investigate the effect of RIPK1 inhibition in advanced atherosclerotic plaque formation, we used ApoESA/SA mice, which exhibit hypercholesterolemia, and develop angiotensin-II mediated hypertension upon administration of doxycycline in drinking water. These mice readily develop severe atherosclerosis, including that in coronary arteries. Eight-week-old ApoESA/SA mice were randomized to orally receive a highly selective RIPK1 inhibitor (RIPK1i, GSK547) mixed with a western diet, or control diet. RIPK1i administration reduced atherosclerotic plaque lesion area at 2 weeks of treatment, consistent with suppressed inflammation (MCP-1, IL-1β, TNF-α) and reduced monocyte infiltration. However, administration of RIPK1i unexpectedly exacerbated atherosclerosis at 4 weeks of treatment, concomitant with increased macrophages and lipid deposition in the plaques. Incubation of isolated macrophages with oxidized LDL resulted in foam cell formation in vitro. RIPK1i treatment promoted such foam cell formation while suppressing the death of these cells. Accordingly, RIPK1i upregulated the expression of lipid metabolism-related genes (Cd36, Ppara, Lxrα, Lxrb, Srebp1c) in macrophage foam cells with ABCA1/ABCG1 unaltered. Furthermore, RIPK1i treatment inhibited ApoA1 synthesis in the liver and reduced plasma HDL levels. Conclusion: RIPK1 modulates the development of atherosclerosis in a stage-dependent manner, implicating both pro-atherosclerotic (monocyte infiltration and inflammation) and anti-atherosclerotic effects (suppressing foam cell accumulation and promoting ApoA1 synthesis). It is critical to identify an optimal therapeutic duration for potential clinical use of RIPK1 inhibitor in atherosclerosis or other related disease indications.